Isolation and characterization of some gut microbial symbionts from fungus-cultivating termites (Macrotermes and Odontotermes spp.) - Budambula, Nancy; Muwawa, Edith M.; Osiemo, Zipporah L.; Boga, Hamadi I.; Makonde, Huxley M. (My University, 2016)
Microbiota of termites is crucial for nitrogen cycle activities and degradation of recalcitrant components of plant biomass that influence soil structure and carbon mineralization in tropical and subtropical regions. The aim of this study was to isolate and characterize gut bacteria that may be potentially associated with nitrogen metabolism from two fungus-feeding termites (Macrotermes and Odontotermes spp.). Twenty termites from the intact colony of each termite species were aseptically degutted. Gut homogenate was inoculated and cultured on selective media for the isolation of pure bacteria. Pure bacterial isolates were characterized using their morphological, biochemical and molecular characters. DNA was extracted from the isolates, polymerase chain reaction (PCR) amplified and sequenced. The 16S rDNA gene sequences were blastn analyzed against the Genbank database and phylogenetic analysis was performed using MEGA 5 software. All forty-six isolates reacted positive for the ammonifying, nitrate, catalase and nitrogenase tests. Phylogenetic analysis grouped the isolates into three phyla: Firmicutes, Proteobacteria and Actinobacteria. Isolates were affiliated with the genera Pseudomonas, Citrobacter, Enterobacter, Proteus, Klebssiella, Bacillus, Staphylococcus, Rhodococcus and Micrococcus. The results confirm that termites harbor diverse gut bacterial groups that have different physiological/enzymatic activities and might have functional implications in the termitemicrobe symbiotic association.
Keywords: Termites; symbiosis; mutualistic interactions; termite gut bacterial diversity; nitrogen fixation